Wykorzystanie badań marketingowych w określaniu wpływu dystrybucji na rynkową wartość przedsiębiorstwa - Czubała, Anna; Jonas, Agata (Marketing Research Use in Defining the Influence of Distribution on Enterprise Market Value, 2006)
In the paper there are presented and arranged essential relationships between distribution and enterprise market value in theory and practice. Basing oneself on interviews and results of questionnaire research conducted in Polish enterprises, there is presented a scope of interest among producers in shaping and controlling distribution channels, distribution strategies they use, forms of cooperation among them and innovations in distribution. Particular attention is paid to the level of consciousness in researched enterprises in relation to the association among distribution, offer value to customers and its competitiveness and enterprise value.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 402-413